2021
DOI: 10.46661/revmetodoscuanteconempresa.3489
|View full text |Cite
|
Sign up to set email alerts
|

Pobreza multidimensional en España. Una aplicación de la metodología de Alkire y Foster. 2008 - 2015

Abstract: Considerando la pobreza como un fenómeno que limita la capacidad de desarrollo de las personas en todas sus dimensiones, se aborda su estudio multidimensional tomando como referencia la metodología de Alkire y Foster (2011). Su aplicación al ámbito español, usando la Encuesta de Condiciones de Vida (ECV2008-ECV2015), genera nueva evidencia sobre la medición de la pobreza multidimensional y su sensibilidad a los criterios de identificación, contribuyendo al debate sobre la pertinencia de esta metodología como r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
(12 reference statements)
0
0
0
Order By: Relevance
“…Gordon thought that concepts like poverty, human rights, or mathematical ability can only be measured indirectly by using suitable indicators and adopting a latent variable approach [12]. Cacabelos et al concluded the increase in multidimensional poverty in the period studied, both in incidence and in intensity, regardless of the selected threshold [13]. In terms of research subjects, White provided a comprehensive overview of the construction of the Multidimensional Poverty Index (MPI), offering a comprehensive analysis of multidimensional poverty in a number of developed economies [14].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Gordon thought that concepts like poverty, human rights, or mathematical ability can only be measured indirectly by using suitable indicators and adopting a latent variable approach [12]. Cacabelos et al concluded the increase in multidimensional poverty in the period studied, both in incidence and in intensity, regardless of the selected threshold [13]. In terms of research subjects, White provided a comprehensive overview of the construction of the Multidimensional Poverty Index (MPI), offering a comprehensive analysis of multidimensional poverty in a number of developed economies [14].…”
Section: Literature Reviewmentioning
confidence: 99%